Reassessing Dwangsom in Indonesian Civil Procedure Law: Legality, Preferences, and Urgency - Setiawan Negara, Dharma; Susilo, Erwin; Lufsiana (UIN Sunan Kalijaga Yogyakarta, 2025)
Dwangsom are intended to compel the losing party to comply with a legally binding court decision. However, in Indonesian civil procedural law, they continue to cause uncertainty and debate. Generally, previous research has focused only enforcement of a fine obstacles rather than on normative limitations, issues with the principle of justice, and the sustainability of dwangsom. This research aims to discuss the legality, preferences, and urgency of Dwangsom through doctrinal legal research methods, drawing on statutory, conceptual, and comparative approaches. The analysis was conducted on Indonesian regulations by comparing them with Dutch civil procedural law as a reference. The findings highlight three key points. First, the application of dwangsom can be traced back to Articles 606a and 606b of the Reglement op de Rechtsvordering (Rv) serve as the primary legal basis for the imposition of dwangsom in Indonesian civil procedure. Second, the principle of proportionality demonstrates that dwangsom should not be applied to judgments involving the payment of a sum of money or debt obligations, because monetary obligations already have their own enforcement mechanism. Third, future reform of Indonesian civil procedure law is necessary to establish measurable standards for determining the dwangsom. The absence of clear limitations regarding the amount and duration of dwangsom creates significant risks of abuse. These findings expand on previous studies by positioning dwangsom as a procedural sanction that must be tested through the principles of proportionality and legal certainty.